If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 3(2x) = 33 Remove parenthesis around (2x) 5x + 3 * 2x = 33 Multiply 3 * 2 5x + 6x = 33 Combine like terms: 5x + 6x = 11x 11x = 33 Solving 11x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '11'. x = 3 Simplifying x = 3
| Y+6(1)=5 | | s-(-13)=46 | | 4=2+2t | | 4(2-x)+5=-3(2x+3)-12 | | n/7-6=14 | | -(b+a)= | | 16cos^4(x)= | | 10(8+x)=260 | | w/-9=5 | | 16(x^3+4x)=0 | | -16p=-64 | | 15(a-7)=-7-8 | | 52x=150 | | 7(x+2)-4m=2(m+10) | | 16cos^4(x)-12cos^2(x)=-1 | | Y+6(-3)=5 | | y-(-6)=53 | | 5x+2d-2x=1 | | 5sinx-4=0 | | u/-9=(-9) | | 2(L+12)=36 | | 3y+2=1-7y | | X-2.4=5.1 | | (p-4)(p+3)=0 | | 16cos^4(x)-12cos^2(x)+1=0 | | 68=t+(-14) | | Z-15=30 | | u-(-14)=19 | | 4*[1-(4-15)/3] | | 6i(4+2i)=equation | | (b-5)(2b-1)=0 | | 5(x+1)-x=4x+5 |